Lightweight foams of amine-rich organosilica and cellulose nanofibrils by foaming and controlled condensation of aminosilane. (24th September 2018) - Gordeyeva, Korneliya; Voisin, Hugo; Hedin, Niklas; Bergström, Lennart; Lavoine, Nathalie
Abstract : Preparation of stable and lightweight hybrid foams from cellulose nanofibrils (TCNFs) and amine-rich organosilane (AS) by controlled sol–gel chemistry of the AS. Abstract : Organosilica foams are commonly formed by a multistep process involving hydrolysis and condensation of organosilanes followed by solvent exchange and e.g. supercritical CO2 drying. Here, we propose a straightforward route to synthesize lightweight hybrid foams from aqueous dispersions of a surface-active aminosilane (AS) and TEMPO-oxidized cellulose nanofibrils (TCNFs). Air bubbles were introduced in the TCNF/AS dispersion by mechanical blending, and the foam was solidified by oven-drying. Evaporative drying at mild temperature (60 °C) resulted in dry foams with low densities (25–50 kg m −3 ), high porosities (96–99%) and macropores of 150–300 μm in diameter. The foaming and foam stabilization were successful for a pH range of 10.4–10.8 for foams containing 55–65 wt% of organosilica in the dry state. The protonation of AS increased the ionic strength of the dispersion and enhanced the interparticle interactions with TCNFs and, in turn, the foam viscosity and foam stability upon drying. The evaporation of water catalyzed the condensation of the AS to form low-molecular linear polymers, which resulted in an increased stiffness and strength of the foam lamella. The crosslinking of the AS polymeric network with the TCNF matrix allowed lightweight and homogeneous macroporous foams to be obtained with controlled densities and high amine content (amine content >4.5 mmol g −1 ) using an environmentally friendly technique.